Reconstructing Political Order Among the Somalis: The Historical Record in the South and Centre. (8th January 2013) - Leonard, David K.; Samantar, Mohamed
Abstract The reconstruction of a larger polity in a violence‐torn society such as Somalia requires negotiation of a new social contract between the superordinate body and the local units of governance that have provided citizens some degree of order throughout the conflict. In this article we show that the very different trajectories for state‐building in the north and south of the country result in good part from different attention to this generalisation. The founding leaders in Somaliland and Puntland consulted extensively with the assemblies of elders and were able to create civilian constitutional orders. Military leaders in the south and central regions did not incorporate their elders into their political systems, even though they controlled similar amounts of territory to their counterparts in the north. Ultimately various Islamic movements did build on community‐level governance and used it to successfully challenge the old 'warlords' but most of those allied with the Transitional Federal Government remain weak at the community base.